The experiences of nurses of infectious and non- infectious wards of caring COVID-19 patients in a big hospital in Iran: A qualitative study - Mehdi Yousefi; Zahra Ebrahimi; Somayeh Fazaeli (Wolters Kluwer Medknow Publications, 2022)
Background: Nurses play a very important role in caring for patients with coronavirus disease-19 (COVID-19). They are on the frontline fighting COVID-19. The objective was to explore the experiences of nurses in the surgical and infectious wards about caring for patients with COVID-19 in a large and tertiary care hospital in Iran. Materials and Methods: This was a qualitative study. Semi-structured qualitative interviews were conducted with 18 nurses in the Imam Reza Hospital Complex from April to May 2020, Mashhad, Iran. Data analysis was performed using the method proposed by Lundman and Granheim. The Maxqda10 software was used. Results: The experiences were summarized into three categories: (1) experiencing new feelings and relationships with colleagues and patients, (2) viewpoints about managers' performance, and (3) concern about getting infected with COVID-19. Findings reflected similar experiences on personal protective equipment between nurses in the surgical and infectious wards. Experiencing new feelings and relationships with colleagues and patients and concern about getting infected and spreading the COVID-19 were mostly expressed by infectious nurses and surgical nurses, respectively. Conclusions: This research results provide evidence of the experiences of infectious and non-infectious disease nurses who are currently caring for COVID-19 patients. Due to some differences between the experiences of these two groups in COVID-19, it is suggested to pay more attention to the needs and required skills in the staff mix during a crisis.